Radionuclides content and the radiological hazard of sediment of the Euphrates River and sprigs-western Iraq - K. Ali, Kamal (Iraqi Journal of Science, 2023)
Sediments samples from ten stations along the Euphrates River and sevensamples from selected springs within Al –Anbar governorate, (western part of Iraq),were collected and analyzed for radioactivity. Sediments samples were dried at 100ºC for 24 hours. Radioactivity in 1 kg of each sample was measured using gammaspectrometer system based on a pure germanium detector with efficiency 30%. Theactivity of Ra-226, Th-232, K-40 were measured to be within the typical average ofthe radioactivity in sediment in world rivers, while relatively elevated concentrationwere found in the sediment of some of the studied spring. In current study activityconcentrations of Cs-137 in the sediments were detected which may be caused bythe global fallout as well as caused by transferring of cesium from the relatively highconcentration areas in western desert by the rainwater within the valleys to thesediments of the Euphrates. The radiological aspects were investigated bycalculating the radiological hazard indices such as absorbed dose rate, annualeffective dose equivalent, hazard indices and gamma index. The radiological hazardindices were below the recommended international values. Ra-226 and Cs-137concentrations in water and radiation doses due to drink water of the EuphratesRiver were estimated. The maximum estimated interior doses which caused by 137Csand 226Ra in water were found to be 1.93 x 10-5mSv/y and 4.01x10-3mSv/y,respectively.